(untitled) (Italian Journal of Public Health, 2007)
Health Impact Assessment is defined as ‘the combination of procedures, methods and tools through which it is possible to evaluate a policy, a program or a development plan concerning possible effects on public health and their distribution in the general population’. In a constructive debate this definition points out some interesting observations: - health is not the result of health policies alone, but it is often defined by the attention given to it in other contexts; - health is however the result of policies and it therefore must deserve the attention of Decision Makers; - health must not be taken into consideration without taking into account an evaluation of its distribution and its determinants within a population. Particular attention must therefore be paid into inequalities; - following the Council of the European Union recent conclusions on Health in All Policies we have to consider that everyday environments such as day-care centers, schools,workplaces,neighborhoods and the commute between them have significant effects on health and that health, in turn, has an effect on the economy by enabling active and productive participation in working life. In the past 20 years huge progress has been achieved in the epidemiological contest to define risks. Nowadays, it is known that a low cultural level lowers the capacity to respond to prevention, that elevated pollution levels do represent a health risk, and that the scarce social relationships that elderly people have in our society have strong consequences on their health and their quality of life.